Sex and alcohol (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Alcohol is widely used and accepted as a pleasure giving substance since ancient time. The ef fects of consumption of alcohol are manifold. In this paper, an attempt has been made to review the work of various authors to find the effects of alcohol especially in sex related activities. The article looks into the effects of alcohol in sexual arousal pattern in both male and female, the effect of alcohol in sexual excitement. The likelihood of a person to consent to sexual intercourse and using alcohol as the excuse for unacceptable sexual behavior and the legal implications of drunken state in sexual assault cases are also discussed.
Keywords: Alcohol; Sex